Migration and consumption - Misuraca, Roberta,Zimmermann, Klaus F. (Global Labor Organization (GLO), 2024)
A scarce literature deals with the consumption implications of cultural assimilation and integration, ethnic clustering and diasporas, the marginal propensity to consume, home production and allocation of time, ethnic consumption, migration, and trade, as well as native consumption responses. Consumption patterns reflect how migrants integrate into their new environment while preserving their cultural origins. The identity formation may also affect economic and societal relations between the involved countries.
10419/289419
Keywords: Graue Literatur; ethnic identity; ethnic imports; ethnic niches; ethnic clusters; diaspora; ethnic goods; cultural assimilation; ethnosizer; consumption propensity; home production; allocation of time